12 | | Normal CTU: |
13 | | * qLx = Reconstruct(q), etc... (for all 6 qxx states) |
14 | | * fx=Riemann_Solve(qLx,qRx), etc... (for all 3 edges) |
15 | | * q2 = q+fx+fy+fz |
16 | | * q2Lx=qLx+fy+fz etc... (for all 6 q2xx states) |
17 | | * f2x=Riemann_Solve(q2Lx,q2Rx) (for all 3 edges) |
18 | | * q3=q+f2x+f2y+f2z |
19 | | |
20 | | Strang split self-gravity: |
21 | | * '''q = q + SG(q, phi)*hdt''' |
22 | | * qLx = Reconstruct(q), etc... (for all 6 qxx states) |
23 | | * fx=Riemann_Solve(qLx,qRx), etc... (for all 3 edges) |
24 | | * q2 = q+fx+fy+fz |
25 | | * q2Lx=qLx+fy+fz etc... (for all 6 q2xx states) |
26 | | * f2x=Riemann_Solve(q2Lx,q2Rx) (for all 3 edges) |
27 | | * q3=q+f2x+f2y+f2z |
28 | | * '''q3=q3+SG(q3, phi)*hdt''' |
29 | | |
30 | | Momentum conserving self-gravity |
31 | | * qLx = Reconstruct(q), etc... (for all 6 qxx states) |
32 | | * ''' qLx(px) =qLx(px)+SG_x(q,phi)*hdt''' |
33 | | * ''' qLy(py) = qLy(py)+SG_y(q,phi)*hdt''' |
34 | | * ''' qLy(pz) = qLy(pz)+SG_z(q,phi)*hdt''' |
35 | | * fx=Riemann_Solve(qLx,qRx), etc... (for all 3 edges) |
36 | | * q2 = q+fx+fy+fz '''+ SG(q,phi)''' |
37 | | * q2Lx=qLx+fy+fz etc... (for all 6 q2xx states) |
38 | | * '''q2Lx=q2Lx+SG_y(q,phi)+SG_z(q,phi)''' (for all 6 q2xx states) |
39 | | * f2x=Riemann_Solve(q2Lx,q2Rx) (for all 3 edges) |
40 | | * '''f2x(p)=f2x(p)+SG_PFlux_x(phi) ''' (same for y and z) |
41 | | * q3=q+f2x+f2y+f2z'''+SG_EFlux_(f2x(rho),f2y(rho), f2z(rho), phi)''' |
42 | | |
43 | | SG_x has two non-zero terms... |
44 | | {{{ |
45 | | #!latex |
46 | | \[ |
47 | | \left [ |
48 | | \begin{array}{c} |
49 | | 0 \\ |
50 | | \rho \nabla_x \phi \\ |
51 | | 0 \\ |
52 | | 0 \\ |
53 | | \rho v_x \nabla_x \phi |
54 | | \end{array} |
55 | | \right ] |
56 | | \] |
57 | | }}} |
58 | | |
59 | | while SG_PFlux_x(phi) has only 1 non-zero term |
60 | | |
61 | | {{{ |
62 | | #!latex |
63 | | \[ |
64 | | \left [ |
65 | | \begin{array}{c} |
66 | | 0 \\ |
67 | | \frac{1}{8G\pi} \left ( (\nabla_x \phi)^2 - (\nabla_y\phi)^2 - (\nabla_z\phi)^2 \right ) + \bar{\rho}\phi \ \\ |
68 | | \frac{1}{4G\pi} \nabla_x \phi \nabla_y\phi \\ |
69 | | \frac{1}{4G\pi} \nabla_x \phi \nabla_z\phi \\ |
70 | | 0 |
71 | | \end{array} |
72 | | \right ] |
73 | | \] |
74 | | }}} |
75 | | |
76 | | and SG_EFlux(f2x, f2y, f2z, phi) is |
77 | | {{{ |
78 | | #!latex |
79 | | \[ |
80 | | \left [ |
81 | | \begin{array}{c} |
82 | | 0 \\ |
83 | | 0 \\ |
84 | | 0 \\ |
85 | | 0 \\ |
86 | | \rho v_x \nabla_x \phi + \rho v_y \nabla_y \phi + \rho v_z \nabla_z \phi |
87 | | \end{array} |
88 | | \right ] |
89 | | \] |
90 | | |
91 | | }}} |
| 3 | Mathematically, we are solving the equation of hydrostatic equilibrium [[latex($\nabla P(r) = -\rho(r) \nabla \phi(r)$)]] subject to the constraint that [[latex($P(R)=P_0$)]]. Since [[latex($\phi(r) = \frac{G M(r)}{r}$)]] we can rewrite the equation for HSE as [[latex($\frac{dP}{dr}=\frac{GM(r)\rho(r)}{r^2}$)]] and we can express the enclosed mass as [[latex($M(r)=4\pi\displaystyle\int_0^r{\rho(r') r'^2dr'}$)]] |
94 | | Making the momentum be conserved requires recasting the gravitational force as a total differential |
95 | | |
96 | | |
97 | | [[latex($\dot p=-\rho \nabla \phi = -\nabla \cdot F$)]] so we need to find [[latex($F$)]] such that |
98 | | |
99 | | [[latex($\nabla \cdot F = \rho \nabla \phi$)]] |
100 | | |
101 | | Since [[latex($\nabla^2 \phi = 4\pi G (\rho-\bar{\rho})$)]] |
102 | | |
103 | | we can substitute for [[latex($\rho$)]] and we have |
104 | | |
105 | | [[latex($\nabla \cdot F = (\frac{\nabla^2\phi}{4 \pi G}+\bar{\rho}) \nabla \phi$)]] |
106 | | which is equivalent (in 1D) to [[latex($\nabla \cdot \left [\frac{1}{2} \frac{\left (\nabla \phi\right )^2}{4 \pi G} + \bar{\rho} \phi \right ]$)]] |
107 | | |
108 | | where we can identify the equivalent momentum flux tensor as [[latex($F=\frac{1}{2} \frac{\left (\nabla \phi\right )^2}{4 \pi G} + \bar{\rho} \phi$)]] |
109 | | |
110 | | |
111 | | * In more than 1D we have |
112 | | |
113 | | {{{ |
114 | | #!latex |
115 | | \begin{align*} |
116 | | \partial_t p_i&=\rho \partial_i \phi \\ |
117 | | & = \left (\frac{\partial_j(\partial_j \phi)}{4 \pi G}+\bar{\rho} \right ) \partial_i \phi \\ |
118 | | & = \frac{\partial_j \left ( \partial_j \phi \partial_i \phi \right) - (\partial_j \phi) \partial_j (\partial_i \phi )}{4 \pi G}+\partial_i (\bar{\rho}\phi) \\ |
119 | | & = \frac{\partial_j \left ( \partial_j \phi \partial_i \phi \right) - (\partial_j \phi) \partial_i (\partial_j \phi )}{4 \pi G}+\partial_i (\bar{\rho}\phi) \\ |
120 | | & = \frac{\partial_j \left ( \partial_j \phi \partial_i \phi \right)}{4 \pi G} - \partial_i\frac{(\partial_j \phi \partial_j \phi)}{8 \pi G}+\partial_i (\bar{\rho}\phi) \\ |
121 | | & = \frac{\partial_j \left ( \partial_j \phi \partial_i \phi \right)}{4 \pi G} - \partial_i\left ( \frac{ \partial_j \phi \partial_j \phi}{8 \pi G} +\bar{\rho}\phi \right) \\ |
122 | | & = \partial_j \frac{\left ( \partial_j \phi \partial_i \phi \right)}{4 \pi G} - \partial_j \left ( \delta^i_j \left ( \frac{\partial_k \phi \partial_k \phi}{8 \pi G} + \bar{\rho}\phi \right) \right ) \\ |
123 | | & = \partial_j T_{ij} \mbox{ where } T_{ij} = \frac{\left ( \partial_j \phi \partial_i \phi \right)}{4 \pi G} - \delta^i_j\left(\frac{\partial_k \phi \partial_k \phi}{8 \pi G}+\bar{\rho}\phi \right) \\ |
124 | | \end{align*} |
125 | | }}} |